Contra ωpre- Continuous functions - B. Jubair, Waqas; J. Ali, Haider (Al-Nahrain Journal of Science, 2022)
In this paper, we present some concepts related to -open set and study some of its basic properties, facts and some examples are given to illustrate our work. Several theoretical results are stated and proved throughout this paper.